Ekstraksi Zat Warna dari Limbah Kulit Kakao sebagai Alternatif Pewarna Batik guna Meningkatkan Produktivitas Masyarakat Agribisnis Desa Banjar Sengon, Kecamatan Patrang - Eriska Eklezia Dwi Saputri; Istiqomah Rahmawati; Rahma Rei Sakura (Universitas Jayabaya, 2022)
Cocoa is commonly found in plantation areas, especially in Patrang sub-district. The Community Service Program, Faculty of Engineering with partners, namely the people of Banjar Sengon Village, aims to overcome partner problems, the increasing cocoa husk waste. Utilization of leather waste is still very limited, where people use cocoa husk waste only as animal feed and compost. Cocoa pods contain cellulose 36.23%, hemicellulose 1.14% and lignin 20 -27.95%. In addition, the presence of anthocyanin pigments in cocoa peel is a potential use of cocoa peel extract as a dye for the batik industry. The implementation method of extraction process is by: (1) socializing about the management and processing of cocoa peel waste, (2) Extracting natural dyes from cocoa peel, (3) socializing the use of natural dyes for batik cloth, (4) activities using natural dyes for batik cloth, and (5) marketing of natural dyes from cocoa peel. The result of this community service program is an increase in the usability of cocoa peel waste which is marked by the people of Banjar Sengon Village being able to process cocoa peel waste into natural batik dyes independently and continuously.